Applying Anti Oppressive, Empowerment, and Strengths Based Approaches to Social Work Practice with Hmong Clients - Serge C Lee; Cindy Vang; Jenny Chang; Pa Der Vang (Asian Social Work Journal, 2021)
This conceptual article discusses social work practice with Hmong Americans using a framework that embraces anti-oppressive practice, empowerment and strengths-based approaches. Specifically, the Hmong kinship social construct of kwv tij neej tsa (pronounced: ku tee ning ja) is used to elaborate on the importance of upholding family relationships that transcends the worker-client relationship. Social workers are encouraged to empower Hmong to seek and ask for resources that support their collective value of connection to family and group identity, which is a strength that contributes to resilience and buffers against historically oppressive practices and systems.